Antimicrobial resistance in Escherichia coli and Pseudomonas aeruginosa before and after the coronavirus disease 2019 (COVID-19) pandemic in the Dominican Republic - Alfredo J. Mena Lora; Chrystiam Sorondo; Belkis Billini; Patricia Gonzalez; Susan C. Bleasdale (Cambridge University Press, 2022)
Abstract Objective: To describe antimicrobial resistance before and after the COVID-19 pandemic in the Dominican Republic. Design: Retrospective study. Setting: The study included 49 outpatient laboratory sites located in 13 cities nationwide. Participants: Patients seeking ambulatory microbiology testing for urine and bodily fluids Methods: We reviewed antimicrobial susceptibility reports for Escherichia coli isolates from urine and Pseudomonas aeruginosa (PSAR) from bodily fluids between January 1, 2018, to December 31, 2021, from deidentified susceptibility data extracted from final culture results. Results: In total, 27,718 urine cultures with E. coli and 2,111 bodily fluid cultures with PSAR were included in the analysis. On average, resistance to ceftriaxone was present in 25.19% of E. coli isolated from urine each year. The carbapenem resistance rates were 0.15% for E. coli and 3.08% for PSAR annually. The average rates of E. coli with phenotypic resistance consistent with possible extended-spectrum β-lactamase (ESBL) in urine were 25.63% and 24.75%, respectively, before and after the COVID-19 pandemic. The carbapenem resistance rates in urine were 0.11% and 0.20%, respectively, a 200% increase. The average rates of PSAR with carbapenem resistance in bodily fluid were 2.33% and 3.84% before and after the COVID-19 pandemic, respectively, a 130% percent increase. Conclusions: Resistance to carbapenems in PSAR and E. coli after the COVID-19 pandemic is rising. These resistance patterns suggest that ESBL is common in the Dominican Republic. Carbapenem resistance was uncommon but increased after the COVID-19 pandemic.